2008
DOI: 10.1186/1471-2164-9-522
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and comparison of Atlantic and Chinook salmon growth hormone 1 and 2

Abstract: Background: Growth hormone (GH) is an important regulator of skeletal growth, as well as other adapted processes in salmonids. The GH gene (gh) in salmonids is represented by duplicated, non-allelic isoforms designated as gh1 and gh2. We have isolated and characterized gh-containing bacterial artificial chromosomes (BACs) of both Atlantic and Chinook salmon (Salmo salar and Oncorhynchus tshawytscha) in order to further elucidate our understanding of the conservation and regulation of these loci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Nevertheless, we also checked the literature for data indicating the presence of regulatory elements in non-coding regions of the GH, IGF-1 and SL genes of other non-Perciformes. It is worth noting that a MAUI-like element has already been reported close to GH genes of fugu and salmonids (Poulter et al 1999;Von Schalburg et al 2008), and a minisatellite observed in the GH gene of Esocidae (Barnett et al 2007). In this latter case, the minisatellite was located in the fourth intron rather than the third intron of sea bass and other species (Fig.…”
Section: Genomic Sequences At Physiologically Important Genes and Assmentioning
confidence: 61%
“…Nevertheless, we also checked the literature for data indicating the presence of regulatory elements in non-coding regions of the GH, IGF-1 and SL genes of other non-Perciformes. It is worth noting that a MAUI-like element has already been reported close to GH genes of fugu and salmonids (Poulter et al 1999;Von Schalburg et al 2008), and a minisatellite observed in the GH gene of Esocidae (Barnett et al 2007). In this latter case, the minisatellite was located in the fourth intron rather than the third intron of sea bass and other species (Fig.…”
Section: Genomic Sequences At Physiologically Important Genes and Assmentioning
confidence: 61%
“…This notion is supported by the fact that IFN-bs and IFN-cs are clustered in the salmon and trout genome (5) and reside in the same locus with the growth hormone (GH) gene 1. Similar gene synteny with the GH1 gene is also seen in zebrafish and Chinook salmon and appears to be conserved more generally in teleosts, cartilaginous fish, and coelacanth (15,36). Salmonids are thought to have undergone an extra whole-genome duplication event compared with other teleost species and often have multiple paralogous genes.…”
Section: Discussionmentioning
confidence: 74%
“…Salmonids are thought to have undergone an extra whole-genome duplication event compared with other teleost species and often have multiple paralogous genes. For example, an additional GH paralogue (GH2) exists and is located in a different chromosomal locus that exhibits little conservation of the functional genes with the GH1 locus and, to date, no clear linkage to IFN genes (36). One of the notable characteristic features of the fish IFN/GH1 locus is that it is transposon rich, which may contribute to the instability of the region and could be the driving force for frequent insertions of duplicated IFN genes, expanding subgroup number, or giving rise to new subgroups locally.…”
Section: Discussionmentioning
confidence: 99%
“…The secretion of GH in fishes is up regulated by growth hormone-releasing hormone (GHRH) and down-regulated by somatostatin (SST). GH was isolated from several teleosts, being considered the major controller of growth of many species (Schalburg et al, 2008;Very et al, 2005). It acts on several physiological processes as gonadal development, osmoregulation, appetite, morphology, social behavior and immunology (Pérez-Sánchez et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It acts on several physiological processes as gonadal development, osmoregulation, appetite, morphology, social behavior and immunology (Pérez-Sánchez et al, 2002). In many fishes, the GH has functions that lacks in others vertebrates as are its effects on sexual maturation (Levy et al, 2010;Schalburg et al, 2008). The SST is classically known to inhibit the secretion of a wide range of hormones including the GH and prolactin.…”
Section: Discussionmentioning
confidence: 99%